2015
DOI: 10.1016/j.gloplacha.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The middle Holocene climatic records from Arabia: Reassessing lacustrine environments, shift of ITCZ in Arabian Sea, and impacts of the southwest Indian and African monsoons

Abstract: A dramatic increase in regional summer rainfall amount has been proposed for the Arabian Peninsula during the middle Holocene (ca. 9-5 ka BP) based on lacustrine sediments, inferred lake levels, speleothems, and pollen. This rainfall increase is considered primarily the result of an intensified Indian summer monsoon as part of the insolation-driven, northward shift of the boreal summer position of the Inter-Tropical Convergence Zone (ITCZ) to over the deserts of North Africa, Arabia, and northwest India.We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 136 publications
(56 reference statements)
3
67
1
Order By: Relevance
“…Achieving these goals will allow SISAL based studies could better constrain teleconnections amongst the hydroclimate of remote regions such as Northern Africa, the Levant and the FC, which should all be influenced by Mediterranean cyclones and ITCZ migration, as the spatial scale of the ITCZ migration and the overall effect it might have had on rainfall amount in the Southern AP is still debated [173] and a regional compilation incorporating crucial missing records to the SISAL database will enable us to shed light on this topic. Furthermore, considering the location of the Levant at the border between the tropical Hadley cell and the mid-latitude Ferrel cell, hydroclimate change in this region is supposed to be very sensitive to shifts in the Hadley-Ferrel-cell border, which should be ultimately imprinted in the speleothem palaeoclimate record.…”
Section: Emphasis For Future Speleothem Research In the Middle Eastmentioning
confidence: 99%
“…Achieving these goals will allow SISAL based studies could better constrain teleconnections amongst the hydroclimate of remote regions such as Northern Africa, the Levant and the FC, which should all be influenced by Mediterranean cyclones and ITCZ migration, as the spatial scale of the ITCZ migration and the overall effect it might have had on rainfall amount in the Southern AP is still debated [173] and a regional compilation incorporating crucial missing records to the SISAL database will enable us to shed light on this topic. Furthermore, considering the location of the Levant at the border between the tropical Hadley cell and the mid-latitude Ferrel cell, hydroclimate change in this region is supposed to be very sensitive to shifts in the Hadley-Ferrel-cell border, which should be ultimately imprinted in the speleothem palaeoclimate record.…”
Section: Emphasis For Future Speleothem Research In the Middle Eastmentioning
confidence: 99%
“…The uppermost part of the sections reflects a period of strong aridity. Enzel et al (2015) regarded the sediment successions of as being wetland deposits.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Several studies such as de Menocal et al (2000), Mischke (2001), Engel et al (2012) and Enzel et al (2015) reported the wet period of the Holocene in a wider area including Arabia, Africa and Asia and discussed the solar cycle effects on Indian monsoon climate. Our record fits a moist period documented for the early to mid-Holocene (Fleitmann and Matter, 2009).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). In order to reach the highest possible sensitivity, to realize a time-efficient prospection and to receive additional information on the enrichment of magnetic minerals in lateral sediment layers, we used the Cs total field magnetometer (Scintrex SM4G-Special) using the "duo-sensor" configuration (see examples in Fassbinder, 2015Fassbinder, , 2017. Five adjacent grids of 40 m × 40 m were prospected.…”
Section: Magnetometer Prospectionmentioning
confidence: 99%